Technical Report A light touch; Reviewing the relative effectiveness of light sources and physical/chemical techniques for fingermark retrieval in casework - Nicholas Marsh; Karen Marsh; Lisa Hall; Ruth Buckley; Stephen Bleay (Forensic Science International: Reports)
This study reviewed the efficacy of non-contact light source examinations of serious crime scenes using ultraviolet A (UVA) light, bespoke white light and lasers, compared with subsequent powdering or chemical enhancements. Twenty-six examinations of serious crime scenes or motor vehicles were analysed, from which 655 areas of retrieved fingermark or friction ridge detail11 Friction Ridge Detail (FRD) relates to deposits made from fingers, phalange, palm or plantar regions. where reported on. It was found that undertaking a light source examination revealed equivalent numbers of marks to aluminium powder and chemical enhancements, with only a 4 % duplication rate between optical and physical/chemical techniques suggesting that both approaches are supplementary and should be used sequentially to each other.